2018
DOI: 10.1002/ams2.364
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory distress syndrome in a patient with AIDS successfully treated with veno‐venous extracorporeal membrane oxygenation: a case report and literature review

Abstract: CaseSeveral successful uses of extracorporeal membrane oxygenation (ECMO) for acute respiratory distress syndrome in patients with novel HIV/AIDS infection have been reported; however, the therapeutic keys have not always been discussed.A 47‐year‐old man was admitted with progressive shortness of breath. He was in respiratory failure with a PaO2/FIO2 ratio of 110.8 requiring intubation. Chest computed tomography showed diffuse ground glass opacities. An HIV infection was suspected, and a diagnosis of acute res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Invasive mechanical ventilation (MV, 40-50% of all admissions), vasopressors (15-30%), and renal replacement therapy for AKI (8-15%) are now used as frequently in seropositive individuals as in the general ICU population [5,7,24,33,43,44], with comparable prognoses including in patients at high risk of death such as those admitted following cardiac arrest or with the acute respiratory distress syndrome (ARDS) [45,46]. Last-resort veno-venous or veno-arterial extracorporeal membrane oxygenation can be discussed in selected patients, with auspicious results in published reports [47,48].…”
Section: Similarities Between Critically Ill Hiv-infected and Seronegmentioning
confidence: 99%
“…Invasive mechanical ventilation (MV, 40-50% of all admissions), vasopressors (15-30%), and renal replacement therapy for AKI (8-15%) are now used as frequently in seropositive individuals as in the general ICU population [5,7,24,33,43,44], with comparable prognoses including in patients at high risk of death such as those admitted following cardiac arrest or with the acute respiratory distress syndrome (ARDS) [45,46]. Last-resort veno-venous or veno-arterial extracorporeal membrane oxygenation can be discussed in selected patients, with auspicious results in published reports [47,48].…”
Section: Similarities Between Critically Ill Hiv-infected and Seronegmentioning
confidence: 99%
“…41,42 More recently, encouraging results were obtained by using veno-venous extracorporeal membrane oxygenation to treat HIV-positive patients with refractory ARDS, suggesting a role for this salvage therapy even in patients with severe immunosuppression. 43,44 Advances in the management of sepsis and septic shock have probably benefited these patients at high risk for severe bacterial infection. 45 Finally, policies promoting the early ICU admission of patients with profound immunosuppression, including HIV-positive individuals, have contributed to improve outcomes.…”
mentioning
confidence: 99%
“…As for the timing of ECLS initiation in PJP, Goodman [10] reported that apart from higher survival rates, the early usage of ECMO during the course of MV can result in a shorter duration of ECMO support in patients. Similarly, Obata [20] also reported that early ECMO introduction can produce early achievement of lung rest management. Capatos G [21] suggested an approach of early ECLS introduction in ARDS patients with AIDS.…”
Section: Discussionmentioning
confidence: 88%
“…Obata. et al [20] 2018 Morley.et al [22] 2018 [26]. The only criteria that is contraindicated for this therapy was reported in the CESAR trial, and it was high pressure (> 30 cm H 2 O of peak inspiratory pressure) and/or high FiO 2 (> 0.8) ventilation > 7 days [7].…”
Section: Discussionmentioning
confidence: 99%